2021
DOI: 10.1021/acsanm.1c02275
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Multiwalled Carbon Nanotube/Polydimethylsiloxane Nanocomposites with Temperature-Controlled, Hydrophobic, and Icephobic Properties

Abstract: Retarding and preventing ice/frost formation have increasing importance in aerospace applications because of widespread energy and safety concerns. In this study, multiwalled carbon nanotube−polydimethylsiloxane (MWCNT/PDMS) nanocomposites were fabricated via mechanical stirring and three-roll grinding. By imitating the microstructures of lotus leaves, various biomimetic nanocomposites were prepared by etching micropillar arrays on MWCNT/PDMS nanocomposites. These biomimetic nanocomposites possess superior fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Electrical devices have been widely employed for active de-icing on a variety of surfaces [6][7][8] and utilize joule heating to raise the temperature of the accreted ice above 0 °C, facilitating its removal through a phase change to liquid water [9][10][11][12] . Proper thermal/electrical conductivity is required to maximize the de-icing efficiency while minimizing energy consumption 9,13,14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical devices have been widely employed for active de-icing on a variety of surfaces [6][7][8] and utilize joule heating to raise the temperature of the accreted ice above 0 °C, facilitating its removal through a phase change to liquid water [9][10][11][12] . Proper thermal/electrical conductivity is required to maximize the de-icing efficiency while minimizing energy consumption 9,13,14 .…”
mentioning
confidence: 99%
“…Electrical devices have been widely employed for active de-icing on a variety of surfaces [6][7][8] and utilize joule heating to raise the temperature of the accreted ice above 0 °C, facilitating its removal through a phase change to liquid water [9][10][11][12] . Proper thermal/electrical conductivity is required to maximize the de-icing efficiency while minimizing energy consumption 9,13,14 . Graphene-based heaters 6,15 , hot air pumping 16 , conductive polymer-based heaters [17][18][19] and, most commonly, metallic heating systems [20][21][22][23] have all been used to provide sufficient heat to melt the interfacial ice.…”
mentioning
confidence: 99%
“…application of bioinspired CNT-based materials in nanopatterned surfaces. 132,133 Liz-Marza ´n et al reported classical sea-anemonelike CNT-based hollow capsules with magnetic and reinforced properties. The CNT-coated Fe 3 O 4 NP@PS spheres were used as the ''hair'' to provide the reinforcement.…”
Section: Nanopatterned Surfacesmentioning
confidence: 99%
“…Besides their potential as reinforcing materials with high mechanical strength and chemical stability, the unique nanoscale morphology, low hydrophilicity, and optical characteristics of assembled structures of CNTs are also instructive for the application of bioinspired CNT-based materials in nanopatterned surfaces. 132,133 Liz-Marzán et al reported classical sea-anemone-like CNT-based hollow capsules with magnetic and reinforced properties. The CNT-coated Fe 3 O 4 NP@PS spheres were used as the “hair” to provide the reinforcement.…”
Section: Applicationsmentioning
confidence: 99%
“…Combined with the surface micro/nano-structures, PDMS substrate can achieve superhydrophobicity, and the ice adhesion strength can be reduced to less than 20 kP a. 13,14 Oil infusion into PDMS substrates can reduce the ice adhesion even further (< 10 kP a). 15 However, the durability of the lubricated PDMS substrate is influenced by the depletion of the lubrication oil layer by the icing-deicing cycles.…”
Section: Introductionmentioning
confidence: 99%